Analyzing the Human Papillomavirus (HPV) Life Cycle in Primary Keratinocytes with a Quantitative Colony‐Forming Assay. Issue 1 (1st May 2014) - Lace, Michael J.; Turek, Lubomir P.; Anson, James R.; Haugen, Thomas H.
Abstract: Papillomavirus genomes replicate as extrachromosomal plasmids within infected keratinocytes, requiring the regulated expression of early viral gene products to initially amplify the viral genomes and subvert cell growth checkpoints as part of a complex path to immortalization. Building on contemporary keratinocyte transfection and culture systems, the methods described in this unit form a detailed approach to analyzing critical events in the human papillomavirus (HPV) life cycle, utilizing physiologic levels of viral gene products expressed from their native promoter(s) in the natural host cells for HPV infection. A quantitative colony‐forming assay permits comparison of the capacities of various transfected HPV types and mutant HPV genomes to initially form colonies and immortalize human keratinocytes. In conjunction with additional methods, these protocols enable examination of genomic stability, viral and cellular gene expression, viral integration, and differentiation patterns influenced by HPV persistence in clonal human keratinocytes that effectively mimic early events in HPV infection. Curr. Protoc. Microbiol . 33:14B.2.1‐14B.2.13. © 2014 by John Wiley & Sons, Inc.